A Global Procurement Partnership for Sustainable Development : An International Stocktaking of Developments in Public Procurement - World Bank (World Bank, Washington, DC, 2022)
Efficient procurement procedures save time and money, opening up much needed fiscal space, yet modern public procurement can also serve as a tool for achieving broader socioeconomic policy change. Government purchasing decisions, including more strategic use of technology, can be used to maximize value for money as defined by a concept of “value” that goes beyond fiscal savings to include broader policy goals such as environmental sustainability, support for small enterprises, or protection of vulnerable groups in society. This report outlines the key challenges and opportunities in moving toward modern procurement systems around the world and makes the case for a global procurement partnership to strengthen development effectiveness through better understanding and implementation of procurement reforms.